A review of the genera Acathrito Lyneborg, Phycus Walker and Salentia Costa (Diptera: Therevidae: Phycinae) from Egypt - Badrawy, Haitham B. M. (Zootaxa, 2013)
The Egyptian fauna of the three genera Acathrito Lyneborg, Phycus Walker and Salentia Costa of subfamily Phycinae (Therevidae) is revised. Five species are recognized, three species of Phycus (including Phycus rufofemoratus Kröber as a new record) and one species for each of Acathrito and Salentia. A key to Egyptian Phycus species is included. Illustrations, specimens examined and distributions are given for each species.